Patient Safety Culture Influence on the Frequency of Reporting Incidents at Hospital - Puspasari, Erin; Harmawati, Harmawati (Mulawarman International Conference on Tropical Public Health, 2025)
Background : In 2023, Pupuk Kaltim Prima Sangatta Hospital recorded 14 patient safety incidents with two Potential Injury Events, three Near Injury Events and nine Undesirable Events. The purpose of this research is to determine the influence of safety culture on the frequency of reporting incidents. Objective : This study aims to asses how various dimensions of safety culture, such as management support, overall perceptions of patient safety, feedback and communication about errors, and openness in communication, impact the reporting of patient safety incidents. Research Methods/ Implementation Methods : The research method used in this study is a non- experimental, descriptive correlational approach with a cross-sectional design. Data were collected through a combination of primary and secondary sources, Primary data collected using the Hospital Survey on Patient Safety Culture (HSOPSC) questionnaire, which assesses various dimensions of safety culture among hospital staff and secondary data based on patient safety incidents recorded hospital database. Results : The study concluded that safety culture has a significant influence on the frequency of incident reporting, with an overall significance value of 0.000 and Management Support for Patient Safety dimension showed a significant impact with a p-value of 0.008, indicating a strong relationship between management support and incident reporting Conclusion/Lesson Learned : The findings highlight the necessity for hospitals to actively promote a culture of safety to encourage staff to report incidents, ultimately leading to improved patient safety outcomes